Between Immigration Control and Child Protection: Unaccompanied Minors in Belgium - Katrien De Graeve; Marianne Vervliet; Ilse Derluyn (Social Work & Society, 2017)
This article describes the situation of Unaccompanied Minors (UAM) in Belgium, both in terms of their numbers and demographic profile and in terms of their health and educational challenges. It sketches the complex Belgian legal and policy framework that determines the organization and the quality of care and support of this particular group of minors. The paper lists policy outcomes, including the creation of a specialized care system for UAM, a guardianship service and a three phase trajectory of observation, stabilization and supported autonomy for most UAM. It also points to policy shortcomings, in particular in relation to UAM's needs. The paper concludes by recommending more research on the experiences and perspectives of UAM and on the variety of psychological, contextual and social factors that influence their wellbeing.